The role of mentoring in research ecosystems in Sub-Saharan Africa: some experiences through the CARTA opportunity (2020)
Mentoring is important for improving capacity development in population and public health research in sub-Saharan Africa. A variety of experiences have been documented since Consortium for Advanced Research Training in Africa (CARTA) admitted the first cohort in 2011. However, the experience of mentoring opportunities in CARTA has not been studied. Our study focused on the perceptions, experiences and challenges of mentoring among CARTA fellows. We adopted a descriptive design based on data collected from the fellows using an online semistructured questionnaire. Out of 143 fellows in the programme, a total of 52 fellows from seven cohorts completed the questionnaire. Fiftythree percent of the respondents were females, more than half belonged to the health sciences while 35% were in the social sciences. Fellows received mentoring from CARTA graduates and experienced researchers in the CARTA network, but they also engaged in peermentoring with one another. Teaching, publishing, conference attendance and grant application were considered particularly important in mentoring, but mentors and mentees highlighted personal and social issues such as networking, work-family life balance, and managing stress and time, as challenges. There is a need for more formalised but flexible mentorship initiative in the CARTA fellowship to facilitate enduring relationships for career development.